2020
DOI: 10.24018/ejbmr.2020.5.3.317
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Entrepreneurial Intention Among Students of The University of The Gambia

Abstract: This paper examined the drivers of entrepreneurial intention among students of the University of the Gambia. Various theories were adopted in the past to study entrepreneurial intentions among university going students. Building on the relevant literature on entrepreneurship models, this research examines student intention to engage in entrepreneurial ventures in the Gambia. In line with several (prior) research, our results confirm the important role of the business climate, entrepreneurial attitude and subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…This combination of factors could stimulate the development of an entrepreneurial mindset, consistent with the principles of Ajzen's Theory of Planned Behavior. Relative to this theory, several studies have attempted to investigate factors that contribute to entrepreneurial attitudes that determine entrepreneurial intentions (Yoon et al, 2011;Israr, Saleem, 2018;Izquierdo, 2013;Fragoso et al, 2019;Manneh et al, 2020;Melhem, Al-shaikh, 2018;Muhammad et al, 2015;Weiss, 2015). In an empirical study, Tong et al (2011) applied convenience sampling techniques and multiple regression analysis to investigate the influences underpinning the formation of an entrepreneurial attitudes among students.…”
Section: Conceptual Framework and Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…This combination of factors could stimulate the development of an entrepreneurial mindset, consistent with the principles of Ajzen's Theory of Planned Behavior. Relative to this theory, several studies have attempted to investigate factors that contribute to entrepreneurial attitudes that determine entrepreneurial intentions (Yoon et al, 2011;Israr, Saleem, 2018;Izquierdo, 2013;Fragoso et al, 2019;Manneh et al, 2020;Melhem, Al-shaikh, 2018;Muhammad et al, 2015;Weiss, 2015). In an empirical study, Tong et al (2011) applied convenience sampling techniques and multiple regression analysis to investigate the influences underpinning the formation of an entrepreneurial attitudes among students.…”
Section: Conceptual Framework and Hypothesis Developmentmentioning
confidence: 99%
“…This could, in turn, provide insights into how open data initiatives could contribute to the achievement of SSDG 8 in these regions. In another 2020 study, Manneh et al (2020) delved into the exploration of factors that shape entrepreneurial intentions among university students in Gambia, Western Africa. The study found that the business environment significantly influences students' attitudes toward entrepreneurial intentions.…”
Section: Conceptual Framework and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This combination of factors could stimulate the development of an entrepreneurial mindset, consistent with the principles of Ajzen's Theory of Planned Behavior. Relative to this theory, several studies have attempted to investigate factors that contribute to entrepreneurial attitudes that determine entrepreneurial intentions (Yoon et al, 2011;Israr, Saleem, 2018;Izquierdo, 2013;Fragoso et al, 2019;Manneh et al, 2020;Melhem, Al-shaikh, 2018;Muhammad et al, 2015;Weiss, 2015). In an empirical study, Tong et al ( 2011) applied convenience sampling techniques and multiple regression analysis to investigate the influences underpinning the formation of an entrepreneurial attitudes among students.…”
Section: Conceptual Framework and Hypothesis Developmentmentioning
confidence: 99%
“…This could, in turn, provide insights into how open data initiatives could contribute to the achievement of SSDG 8 in these regions. In another 2020 study, Manneh et al (2020) delved into the exploration of factors that shape entrepreneurial intentions among university students in Gambia, Western Africa. The study found that the business environment significantly influences students' attitudes toward entrepreneurial intentions.…”
Section: Conceptual Framework and Hypothesis Developmentmentioning
confidence: 99%